The Relationship between Green Supplier Development Strategies and Firm Performance - Khoo, Bao Ming; Wan Ahmad, Wan Nurul Karimah; Shamsuddin, Alina (Research in Management of Technology and Business, 2021)
Society nowadays is more concerned about environmental issues compared to the previous generations. Companies, especially in the manufacturing sector, are considered as one of the main contributors to the rise of environmental issues caused by their supply chains activities. Having suppliers that are equipped with green capabilities can help companies reduce their supply chain impact. This study focuses on identifying the relationship between green supplier development strategies and firm performance. A survey was conducted among 370 manufacturing companies in Malaysia, where 58 questionnaires distributed to the companies were returned. Data collected were analysed using descriptive and correlation analysis. The results show that information sharing and training for supplier have a high relationship with firm environmental performance. In addition, good relationship between companies and their suppliers tend to increase economic performance.